The Algorithmic Pharmacist: How Professionals Master AI Drug Systems - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into the pharmaceutical landscape is no longer a future concept; it is a present reality. From accelerating dru...
Keywords: Drug Discovery; Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care